A technical and economic feasibility study on repurposing copper mine tailings via microbial induced calcium carbonate precipitation - De Oliveira, Daniel (Department of Civil Engineering, 2021)
The current manufacturing of clay-fired and cement bricks has contributed greatly to anthropogenic global emissions and environmental damages. A possible solution that could be used to alleviate such environmental pressures is through the adoption of carbon neutral, microbial induced calcium carbonate precipitation (MICP) bio-bricks as a replacement for traditional bricks. MICP produced bio-bricks are formed by exploiting the ability of the microorganism, Sporosarcina pasteurii, to produce a biocement capable of binding sand particles (or any aggregate) together into a solid. Furthermore, such bio-bricks can be grown from otherwise ‘waste' resources such as human urine. This significantly reduces energy inputs whilst creating value by ‘upcycling' waste streams, resulting in a product which is sustainable whilst promoting the modern ethos of implementing environmentally friendly circular economies. However, the environmental benefits of MICP bio-bricks are hindered by the use of sand in their production. Sand, after water, is by volume the worlds most exploited and traded raw material and as such the supply of sand is being rapidly depleted globally. Added to this, sand extraction processes are known to cause extensive environmental damages. A possible solution to this issue is to replace the sand aggregate used to grow bio-bricks with mine tailings. The increasing global demand for metal products has resulted in the concurrent production of vast volumes of waste mine tailings which, if left untreated, pose a potential risk of leaching toxins into surrounding populations and biota. As such it was postulated that this risk to surrounding populations and the environment could be mitigated by repurposing mine tailings, as a replacement for sand, into MICP bio-bricks. Both a technical and economic study was conducted to determine the feasibility of repurposing copper mine tailings into bio-bricks. As bio-bricks were resource intensive to produce (reagents, chemicals etc.), bio-columns were used as a proxy in studying the technical feasibility of such a process. The technical aspect of this study involved characterising copper mine tailings received from Columbia in terms of physiochemical make-up, particle size distribution and the development of a MICP submergent technique used in growing the bio-columns. This was necessitated by the fact that it was noted during the characterisation of the mine tailings that the cementation media could not be pumped through the columns filled with mine tailings aggregate, resulting in the traditional pumping method used to grow MICP bio-solids being impractical. The submergent technique was used to compare the MICP efficiency of growing biocolumns from either beach sand or copper mine tailings. In addition, the toxicity of copper to S. pasteurii was investigated and an attempt was made to acclimate a culture of S. pasteurii to the copper concentration found within copper mine tailings. Furthermore, the copper mine tailings were screened to determine if there were any indigenous, anaerobic and copper tolerant ureolytic extremophiles contained within, which had the potential to grow more robust bio-columns.